Does Value Congruence Mediate the Relationship between Service Trust and Use of Fintech? - Effendi, Laij Victor; Radianto, Wirawan Endro Dwi (International Business Management - Universitas Ciputra, 2022)
This study aims to investigate the effect of service trust on fintech use through value congruence as a mediating variable. Writers use women as a sample because women make more purchasing decisions than men. The research method used is the survey method by sending questionnaires to respondents. This study found that women with high service trust will be more encouraged to use fintech. Quality, effective, and efficient fintech will mediate the effect of service trust on fintech use. Writers also found that women who already believe in fintech will immediately be able to increase the use of fintech without mediating value congruence. However, to increase the use of fintech, this study found that it could be done through value congruence. Thus, value congruence has an essential role in increas- ing the use of fintech. Keywords: value congruence, service trust, fintech use, fintech, woman